Pengaruh Artificial Intelligence Marketing dan Content Marketing Terhadap Minat Beli dan Keputusan Pembelian - Viki Ahmad Badri; Miftahul Huda (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to determine the influence of Artificial Intelligence Marketing and Content Marketing on Purchase Interest and Purchase Decisions of Digital MSME Consumers in Pasuruan Regency. The type of research used in this research is explanatory research with a quantitative approach. The sampling technique was carried out using Non Probability Sampling with a purposive sampling technique. The total sample in this research was 114 respondents. Data collection was carried out by distributing questionnaires directly to Digital MSME customers in Pasuruan Regency who were the research objects. The data obtained in this research were analyzed using Structural Equation Modeling (SEM) analysis techniques based on the PLS (Partial Least Square) variant with the help of SmartPLS 4.0 software. Testing of this research model was carried out using outer model (measurement model) and inner model (structural model) tests. The results of this research show that the Artificial Intelligence Marketing variable has a positive and significant influence on Purchase Interest, Content Marketing has a positive and significant influence on Purchase Interest, Artificial Intelligence Marketing has a positive and significant influence on Purchase Decisions, Content Marketing has a positive and significant influence on Purchase Decisions Purchase Interest influences positive and significant on Purchasing Decisions.